A STUDY ON THE LISTENING COMPREHENSION ABILITY OF THE SECOND YEAR STUDENTS OF ENGLISH STUDY PROGRAM FKIP UNIVERSITAS RIAU - Ridarta, Adel; Azhar, Fadly; Eliwarti, Eliwarti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is aimed to find out the listening comprehension ability of the second year students of English Study Program FKIP Universitas Riau. The population of this research is the second year students of English Study Program FKIP Universitas Riau. The number of sample is 34 students selected by using cluster random sampling technique. The instrument to collect the data were multiple choice test items with 15 questions and true or false test items with 15 questions. The test constructed by referring to the components of listening comprehension that is listening to specific information, listening for main idea, listening for inference, listening for making evaluation, and listening for making appreciation. The data were analyzed by classifying them into four levels of mastery, such as poor, poor to average, average to good, and good to excellent. Based on the findings this research, it was found that the students’ listening comprehension ability of the second year students of English Study Program FKIP Universitas Riau was in average to good level with the mean score was 70.3. The implication of this research is that the second year students of English Study Program FKIP Universitas Riau have a good ability in listening comprehension.Key Words: Students’ ability, Listening comprehension